Bioconcentration and metabolism of BDE-209 in the presence of titanium dioxide nanoparticles and impact on the thyroid endocrine system and neuronal development in zebrafish larvae. Issue 1 (August 2014) - Wang, Qiangwei; Chen, Qi; Zhou, Peng; Li, Wenwen; Wang, Junxia; Huang, Changjiang; Wang, Xianfeng; Lin, Kuangfei; Zhou, Bingsheng
Abstract Interactions between organic toxicants and nanoparticles (NPs) in the aquatic environment may modify toxicant bioavailability and consequently the toxicant's environmental fate and toxicity. Therefore, we investigated the influence of titanium dioxide NPs (nano-TiO2) on deca-BDE (BDE-209; a polybrominated diphenyl ether congener) bioconcentration, metabolism and its effects on the thyroid endocrine system in zebrafish (Danio rerio) larvae. Zebrafish embryos were exposed to various concentrations of BDE-209 alone or in combination with nano-TiO2 (0.1 mg/L) until 7-day post-fertilization. Nano-TiO2 can adsorb BDE-209 and nano-TiO2 is taken up into developing zebrafish larvae. Chemical measurements showed that BDE-209 was bioconcentrated and metabolized in zebrafish larvae, and BDE-209 uptake was enhanced by nano-TiO2. Furthermore, increased BDE-209 metabolites were detected in larvae co-exposed with nano-TiO2. BDE-209 exposure significantly increased whole-body thyroid hormone contents (T3 and T4); T4 content significantly increased in the larvae co-exposed with nano-TiO2. Nano-TiO2 exposure alone did not induce generation of reactive oxygen species, lipid peroxidative oxidation, gene transcription or thyroid hormone levels. Upregulation of several gene transcriptions (tshβ, tg, dio2) in the hypothalamic–pituitary–thyroid axis was also observed. Furthermore, co-exposure of nano-TiO2 and BDE-209 caused a decrease in locomotion activity and downregulation of specific genes and proteins involved in the central nervous system of developing zebrafish larvae (e.g. myelin basic protein and α1-tubulin). These results indicate nano-TiO2 enhances BDE-209 bioavailability and metabolism, leading to thyroid endocrine disruption and developmental neurotoxicity in zebrafish.